The Rise and Fall of an African Utopia A Wealthy Theocracy in Comparative Perspective - Barrett, Stanley; Barrett, Stanley (Wilfrid Laurier University Press, 2006)
In 1947 a group of Yoruba-speaking fishermen who had been persecuted because of their religious beliefs founded their own community in order to worship in peace. Although located in an impoverished part of Nigeria, within a few years the village enjoyed remarkable economic success. This was partly because the fishermen held all goods in common, pooled the profits in the community treasury, and attempted to reduce the importance of the family and marriage. After about a generation the utopia began to fall apart. The early religious zeal faded, private enterprise replaced communalism, and the family became strong once more. In an attempt to explain the initial success and eventual decline of the utopia, the author compares it with neighbouring villages that embraced similar religious beliefs but did not enjoy the same economic success. He sets the problem firmly in a broad comparative framework and draws the implications for theories of development, especially Weber$1 (Bs Protestant ethic thesis.s